Konsep Ketuhanan dalam Filsafat Ibn ʻArabī dan Meister Eckhart: Dialektika antara Transendensi dan Immanensi - Marlichasia Marlichasia; Ferdinand Saputra; Afdol Salam; Jubaidah Fatmawati (Kamali: Jurnal Ilmu Agama, 2025)
Understanding the concept of God in two major traditions—Islam and Christianity—has profound philosophical and theological significance, especially when examined through the mystical thought of Ibn ʻArabī and Meister Eckhart, who both position God as the highest reality in the dialectic between transcendence and immanence. This study aims to analyze and compare the metaphysical, epistemological, and anthropological structures of the concept of God in these two figures to reveal patterns of unity and difference in how they interpret the relationship between God, the world, and humans. Using a qualitative approach and a philosophical-comparative hermeneutic method, this study explores primary texts such as Ibn ʻArabī ’s Fuṣūṣ al-Ḥikam and al-Futūḥāt al-Makkiyyah, as well as Meister Eckhart’s sermons and tracts, accompanied by an analysis of relevant secondary literature. The results of the study show that metaphysically, Ibn ʻArabī affirms Absolute Wuju d as a single reality that manifests itself through tajallī in all forms of existence, while Eckhart understands Godhead as the “Divine foundation” that transcends all categories but simultaneously gives birth to the world through a dynamic emanative process. In the epistemological realm, Ibn ʻArabī views knowledge of God as realized through direct experience (kashf) of Divine manifestations, while Eckhart emphasizes the “birth of the Word” in the soul as a process of inner union with God. Anthropologically, both see humans as microcosms and mirrors of the Divine in which God reflects Himself. This study concludes that the thoughts of Ibn ʻArabī and Meister Eckhart demonstrate a dialectical structure of the Divine, where transcendence and immanence are harmoniously combined in a single and inseparable metaphysical reality.